Compositional Quality and Potential Gastrointestinal Behavior of Probiotic Products Commercialized in Italy - Vecchione, Alessandra; Celandroni, Francesco; Mazzantini, Diletta; Senesi, Sonia; Lupetti, Antonella; Ghelardi, Emilia (Frontiers in Medicine, 2018)
Recent guidelines indicate that oral probiotics, living microorganisms able to confer a health benefit on the host, should be safe for human consumption, when administered in a sufficient amount, and resist acid and bile to exert their beneficial effects (e.g. metabolic, immunomodulatory, anti-inflammatory, competitive). This study evaluated quantitative and qualitative aspects and the viability in simulated gastric and intestinal juices of commercial probiotic formulations available in Italy. Plate counting and MALDI-TOF mass spectrometry were used to enumerate and identify the contained organisms. In vitro studies with two artificial gastric juices and pancreatin-bile salts solution were performed to gain information on the gastric tolerance and bile resistance of the probiotic formulations. Most preparations satisfied the requirements for probiotics and no contaminants were found. Acid resistance and viability in bile were extremely variable depending on the composition of the formulations in terms of contained species and strains. In conclusion, this study indicates good microbiological quality but striking differences in the behavior in the presence of acids and bile for probiotic formulations marketed in Italy.